Design of a cluster-randomized minority recruitment trial: RECRUIT. (June 2017) - Tilley, Barbara C; Mainous, Arch G; Smith, Daniel W; McKee, M Diane; Amorrortu, Rossybelle P; Alvidrez, Jennifer; Diaz, Vanessa; Ford, Marvella E; Fernandez, Maria E; Hauser, Robert A; Singer, Carlos; Landa, Veronica; et al.
Background: Racial/ethnic minority groups remain underrepresented in clinical trials. Many strategies to increase minority recruitment focus on minority communities and emphasize common diseases such as hypertension. Scant literature focuses on minority recruitment to trials of less common conditions, often conducted in specialty clinics and dependent on physician referrals. We identified trust/mistrust of specialist physician investigators and institutions conducting medical research and consequent participant reluctance to participate in clinical trials as key-shared barriers across racial/ethnic groups. We developed a trust-based continuous quality improvement intervention to build trust between specialist physician investigators and community minority-serving physicians and ultimately potential trial participants. To avoid the inherent biases of non-randomized studies, we evaluated the intervention in the national Randomized Recruitment Intervention Trial (RECRUIT). This report presents the design of RECRUIT. Specialty clinic follow-up continues through April 2017. Methods: We hypothesized that specialist physician investigators and coordinators trained in the trust-based continuous quality improvement intervention would enroll a greater proportion of minority participants in their specialty clinics than specialist physician investigators in control specialty clinics. Specialty clinic was the unit of randomization. Using continuous quality improvement, the specialist physician investigators and coordinators tailored recruitment approaches to their specialty clinic characteristics and populations. Primary analyses were adjusted for clustering by specialty clinic within parent trial and matching covariates. Results: RECRUIT was implemented in four multi-site clinical trials (parent trials) supported by three National Institutes of Health institutes and included 50 associated specialty clinics from these parent trials. Using current data, we have 88% power or greater to detect a 0.15 or greater difference from the currently observed control proportion adjusting for clustering. We detected no differences in baseline matching criteria between intervention and control specialty clinics (all p values > 0.17). Conclusion: RECRUIT was the first multi-site randomized control trial to examine the effectiveness of a trust-based continuous quality improvement intervention to increase minority recruitment into clinical trials. RECRUIT's innovations included its focus on building trust between specialist investigators and minority-serving physicians, the use of continuous quality improvement to tailor the intervention to each specialty clinic's specific racial/ethnic populations and barriers to minority recruitment, and the use of specialty clinics from more than one parent multi-site trial to increase generalizability. The effectiveness of the RECRUIT intervention will be determined after the completion of trial data collection and planned analyses.